Phase I Clinical Evaluation of rDEN4Δ30-200,201: A Live Attenuated Dengue 4 Vaccine Candidate Designed for Decreased Hepatotoxicity - McArthur, Julie H. (2008)
The rDEN4Δ30-200,201 is a live attenuated DENV-4 vaccine candidate specifically designed to further attenuate the rDEN4Δ30 parent virus. In the present study, 28 healthy adult volunteers were randomized to receive either 10(5) plaque-forming unit (PFU) of vaccine (20) or placebo (8) as a single subcutaneous injection. Volunteers were evaluated for safety every other day for 16 days. Serum neutralizing antibody titer against DEN4 was determined at study day 28, 42, and 180. The vaccine infected all vaccinees and was well tolerated without inducing alanine aminotransferase (ALT) elevations. Although virus was not recovered from the serum of any vaccinee, moderate levels of neutralizing antibody were induced in all volunteers. Thus the restricted replication of rDEN4Δ30-200,201 previously documented in animal models was confirmed in humans. The rDEN4Δ30-200,201 is a promising candidate and can be considered for inclusion in a tetravalent dengue virus (DENV) vaccine.